Positioning students as (non)writers: A case study of disengaged pedagogy in a suburban primary school - O'Leary, Rachel (School of Education, 2018)
Given the challenges facing the South African education system, suburban schools are often assumed to be sites of excellence, and therefore seldom the objects of research. This notion, as well as the persistently poor literacy rates in South African primary schools and the need for more research on the teaching and learning of writing at the upper-primary level across school systems, motivates this case study. This research maintains a sociocultural view of literacy and learning. The linguistic ethnographic approach, carried out with classroom observations, field notes, video-recording and semi-structured interviews, necessitated particular attention to the specific practices of this 'niche' (Nystrand, Gamoran & Carbonaro, 1998) environment. Therefore, although I planned to analyse classroom discourses and students' writing to determine if and how students identify as writers, the teacher's profound disengagement with her pedagogy, her dominant procedural discourse and the closing down of opportunities for her students to take up positions as writers needed to be centred. This focus was particularly important, as in the broader context of her school and the South African education system, Miss King is perceived to be a 'good teacher;' this notion was substantiated by the feedback Miss King received from the Department of Basic Education representative who inspected the school during my field work. Critical Discourse Analysis (Gee, 2008; Janks, 1997; Rogers et al., 2005), Positioning Theory (Davies & Harré, 1990) and Ivanič's (2004) Discourses of Writing were used as conceptual resources in the analysis of the data gathered. These tools enabled an examination of how the participants in a Grade 6 classroom use and navigate discourses to position themselves and others. The teacher self positioned as the authoritative 'knower' through her use of monologic speaking turns and a restrictive Initiation-Response-Evaluation discoursal structure. Despite her assessment driven language and her insistence on students using the process approach when writing, her disengagement from her pedagogy, inability to talk about her learners as writers and unnecessarily prescriptive parameters for compositions, demanded an adaptation of Ivanič's Discourses of Writing framework; in order to capture the superficiality of her discourse, I have added a 'procedural discourse' category. Through this discourse, Miss King can be seen to position her students as nonwriters. In spite of the limiting opportunities to engage meaningfully with their teacher and their learning, the students' abilities to reposition themselves illustrate their continued agency in this space. That they control the classroom discourses during writing sessions, after the teacher delivers her introductions, demonstrates their power in this classroom, their ability to manage their teacher. Still, that some students are able to resist Miss King's positioning to maintain identities as writers occurs despite her pedagogy, not because of it; and those who struggle to reposition themselves are unfairly denied access to identities that should be open to them within the space of the classroom.